Efektivitas Metode Token Ekonomi dalam Meningkatkan Perilaku Disiplin pada Siswa Kelas IV SDN (The Effectiveness of the Token Economy Method in Improving Disciplinary Behavior among Fourth-Grade Students at SDN) - Denisa Yulianti,; Huda, M. Qomarul; Mirwani, Shofi (Happiness: Journal of Psychology and Islamic Science, 2025)
Discipline is a form of students’ attitudes and behaviors in the school environment that reflects obedience to rules, self-control, and commitment to fulfilling responsibilities with full awareness. However, observations of fourth-grade students at SDN Satak 2 revealed a lack of disciplinary behavior, such as not wearing the prescribed uniform, failing to complete assignments on time, not maintaining order during learning activities, and neglecting classroom duty schedules. These behavioral issues encouraged the researcher to implement a token economy intervention. This study aimed to examine whether the token economy method could improve the disciplinary behavior of fourth-grade students at SDN Satak 2 Puncu, Kediri. This study employed a quantitative method with an experimental approach using a one-group pretest–posttest design. Data were collected through questionnaires, observations, and documentation. The population of this study consisted of all fourth-grade students at SDN Satak 2, totaling 14 students, and the sample included the entire population using a saturated sampling technique. The results showed an increase in the mean score from 43.79 in the pretest to 62.86 in the posttest. The Wilcoxon Signed-Rank Test yielded a significance value of 0.001 (p < 0.05), indicating a statistically significant difference before and after the implementation of the token economy method. The N-Gain value was 0.7986, which falls into the high category, indicating a substantial improvement in scores. Therefore, the token economy method is proven to be effective in improving the disciplinary behavior of fourth-grade students at SDN Satak 2 Puncu, Kediri.